Propertis Psikometris Skala Sikap Terhadap Pelajaran Sosial Humaniora - Jelpa Periantalo (Jurnal Ilmu Perilaku, 2017)
The purpose of research was to assess psychometric properties of scale attitude toward social sciences subject: Economics, Sociology, History and Geography. Psychometric properties consisted of validity, reliability and item discrimination. The subjects were 198 high school students with purposive sampling method. Scale used semantic differensial format with overall 68 items. One item unpassed, 67 items passes selection with rit ≥ 0,400. Factorial validity confirmed 3 assumed factors: activity, evaluation and potential. Convergent validity showed positive correlation among subscale. The parallel test reliability showed of equivalent coefficient rxx’ 0,939. The final scale consisted of 12 items, easily in used and scoring. The scale could be used for research, external validation of other scale, high school majoring, educational counseling, learning evaluation, education intervension and university majoring. The next research was to validate with external criterion especially academic achievement.